Frequency of bleeding complications in Algerian patients treated with the vitamin K antagonist acenocoumarol and associated factors - Belkacemi, Malika; Merad, Yassine; Berber, Abdellah (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The major complication of vitamin K antagonist (VKA) therapy is bleeding. This study aimed to estimate the rate of hemorrhagic accidents and identify the hemorrhagic factors in Algerian patients treated by the VKA, acenocoumarol. Methods: We performed a cross-sectional study in patients undergoing VKA therapy, followed in the cardiology department of the University Hospital of Sidi Bel Abbes. Results: One hundred patients were included. We recorded 22 cases of bleeding. Overdose and concomitant use of drugs that interfere with the acenocoumarol effect are significant risk factors of bleeding. Conclusions: Knowledge of predictive factors for VKA-related excessive anticoagulation seems to be of the utmost importance for improving patient management. There is a need for a national registry to assess the efficacy and safety of drug use in the short and long term. This pilot study is a cornerstone in the development of oral anticoagulation therapy monitoring in our region.